Acute kidney injury in patients with decompensated cirrhosis: knowing the cause is often difficult - Rahman, Mohammed Faisal; Szerlip, Harold M. (AME Medical Journal; Vol 3 (September 2018): AME Medical Journal, 2018)
Acute renal failure (AKI), which occurs in up to 20–50% of patients hospitalized with decompensated cirrhosis is an important predictor of poor outcomes and mortality (1,2). The etiology of AKI in these patients has been divided into a functional decrease in renal function; as is in pre-renal azotemia (PRA) and Hepato-renal syndrome (HRS) or structural abnormalities as is in acute tubular necrosis (ATN).